Influence of praseodymium on a solid - state oxidation kinetics of Al +6%Li alloy. (2020) - Nazarov, Sh.; Ganiev, I.; Calliari, I.; Gafarov, A.; Nazarov, D.; Yunusov, F.
Abstract: This article describes the results of thermogravimetric analysis of the oxidation kinetics of Al +6% Li alloy modified by praseodymium in amount up to 0.5%. It is demonstrated that the addition of praseodymium to the alloy or an increase in temperature provides an increase in the oxidation rate of the initial alloy in the solid state. The apparent oxidation activation energy of the initial (basic) alloy (35.2 kJ/mol) decreases to17.3 kJ/mol for the alloy with 0.5% Pr. The oxidation curves of Al +6% Li + Pr alloys in the solid state are described by equations evidencing a hyperbolic mechanism of this process.